Удосконалення залізничних пасажирських перевезень у приміському сполученні на дільниці Л-М у зв’язку з впровадженням швидкісних електропоїздів - Югас, Ігор Ярославович; Yuhas, Ihor Yaroslavovych (Національний університет "Львівська політехніка", 2024)
Головне завдання працівників залізничного транспорту полягає у тому щоб забезпечити рух пасажирських поїздів суворо по розкладу, безпеку пасажирів, високу культуру їх обслуговування, надання максимальної кількості послуг. Від їх знань та уміння використовувати передові методи праці, багато в чому залежить і успішне вирішення задач, які поставлені перед залізничним транспортом України [1]. Пасажирські перевезення – це один з основних видів діяльності залізничного транспорту. Залізничний транспорт був і залишається в Україні найбільш ефективним перевізником вантажів і пасажирів. На долю пасажирських перевезень приходиться біля 40% пасажирообороту від всього пасажирообороту, що виконується транспортом загального користування [2]. З наведених розрахунків [3] можна зробити висновок, що вітчизняний ШРС ЕКр1 «Тарпан» має високий рівень конкурентоспроможності в порівнянні з багатьма ШРС інших країн. За результатами виконання бакалаврської кваліфікаційної роботи проведено аналіз особливостей техніко-економічних показників швидкісних електропоїздів ЕКр-1 Тарпан і вимог до процесу його експлуатації на ділянці Л-М. Це визначає доцільність подальшого розвитку інфраструктури системи утримання ШРС на базі власного виробництва з поступовим освоєнням організації утримання закордонного ШРС на власній ремонтній базі своїм ремонтним персоналом [4]. Метою роботи є підвищення ефективності приміських залізничних пасажирських перевезень на дільниці Львів-Мостиська. 5 Об'єктами дослідження у цій роботі є рухомий склад для пасажирських перевезень, інфраструктура тягового плеча Л-М, що пов’язана з обслуговуванням пасажирів, експлуатація рухомого складу на цієї ділянці. Предметом дослідження є доцільність впровадження руху швидкісних електропоїздів ЕКр-1 на ділянці Л-М.

The main task of railway transport workers is to ensure the movement of passenger trains strictly according to the schedule, passenger safety, a high culture of their service, and the provision of the maximum number of services. The successful solution of the tasks set for the railway transport of Ukraine largely depends on their knowledge and ability to use advanced work methods [1]. Passenger transportation is one of the main types of railway transport activity. Railway transport has been and remains the most effective carrier of goods and passengers in Ukraine. Passenger transportation accounts for about 40% of the passenger turnover of the total passenger turnover carried out by public transport [2]. From the above calculations [3] it can be concluded that the domestic EKr1 "Tarpan" electric train has a high level of competitiveness compared to many other countries' electric trains. Based on the results of the bachelor's qualification work, an analysis of the features of the technical and economic indicators of the EKr-1 Tarpan high-speed electric trains and the requirements for the process of its operation on the L-M section was carried out. This determines the feasibility of further development of the infrastructure of the electric train maintenance system based on its own production with the gradual mastering of the organization of maintenance of foreign electric trains on its own repair base by its repair personnel [4]. The purpose of the work is to increase the efficiency of suburban railway passenger transportation on the Lviv-Mostyska section. The objects of research in this work are rolling stock for passenger transportation, the infrastructure of the L-M traction arm, which is associated with passenger service, and the operation of rolling stock on this section. The subject of the study is the feasibility of introducing high-speed electric trains EKr-1 on the L-M section. 7
Improvement of rail passenger transportation in commuter transportation on the L-M section due to the introduction of high-speed electric trains
Keywords: 6.275.02.04; електропоїзд; моторвагонне депо; технічні характеристики; приміські перевезення; залізничний транспорт; реформування приміських перевезень; техніко-економічні показники; electric train; railcar depot; technical characteristics; suburban transportation; railway transport; reform of suburban transportation; technical and economic indicators. List of used literature sources 1. National Transport Strategy of Ukraine for the period until 2030. Approved by the order of the Cabinet of Ministers of Ukraine dated May 30; 2018 No. 430-р. [Electronic document]. Access mode: http://zakon.rada.gov.ua/laws/show/430-2018-%D1%80 2. Chygrinov V.V. Results of the analysis of trends in the development of railway transportation in Ukraine [Electronic document]. Access mode: https://economyandsociety.in.ua/index.php/journal 3. Methodological instructions on the discipline: “Passenger transportation by rail” for completing a coursework on the topic “Organization of passenger transportation in suburban services” [Text] / S. V. Grevtsov.– Lviv: NULP; 2023. – 41 p. 4. Kravtsov V.O. High-speed rolling stock: technical operation and maintenance. – Lviv: LDUT; 2019. – 314 p